2015
DOI: 10.1016/j.jcct.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ventricular function by CT

Abstract: The assessment of ventricular function, cardiac chamber dimensions and ventricular mass is fundamental for clinical diagnosis, risk assessment, therapeutic decisions, and prognosis in patients with cardiac disease. Although cardiac computed tomography (CT) is a noninvasive imaging technique often used for the assessment of coronary artery disease, it can also be utilized to obtain important data about left and right ventricular function and morphology. In this review, we will discuss the clinical indications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…150,151 Both RV and LV volumes and EF can be obtained from an electrocardiographically gated scan. 137,138,[152][153][154] It can also be used in patients who are being evaluated for cardiac resynchronization therapy and upgrade to a biventricular pacing system. 155 Indications for CT in patients with TGA are listed in Table 10.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…150,151 Both RV and LV volumes and EF can be obtained from an electrocardiographically gated scan. 137,138,[152][153][154] It can also be used in patients who are being evaluated for cardiac resynchronization therapy and upgrade to a biventricular pacing system. 155 Indications for CT in patients with TGA are listed in Table 10.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Arrhythmogenic RV cardiomyopathy (ARVD) is characterized by fibrofatty replacement of the RV with variable involvement of the LV and presents clinically as arrhythmias, typically at a young age. While CT may show fat in the RV myocardium, contributing diagnostic findings at imaging according to Task Force criteria include the presence of major wall motion abnormalities (akinesia, dyskinesia, or dyssynchrony) with either a dilated RV (enddiastolic volume greater than 110 mL/m 2 for male, greater than 100 mL/m 2 for female) or RV dysfunction (ejection fraction less than 40%) ( Figure 9) (79,80) .…”
Section: A B Cmentioning
confidence: 99%
“…Cardiac CT is also valuable in assessing the volumes and function of other cardiac chambers, including the RV (91). CT has been shown to be accurate compared to MRI in the evaluation of RV volumes and functions (79,92,93), particularly in patients who cannot have MRI, since echocardiography provides limited acoustic windows in adults for the evaluation of RV. Atrial volumes and function can also be quantified using CT (94).…”
Section: Quantification Of Cardiac Volumes and Functionmentioning
confidence: 99%
“…This dose modulation protocol allows reconstruction of an end systolic dataset with sufficient image quality to detect the endocardial contours in addition to a high quality diastolic dataset. Prospectively ECG-triggered datasets can also be used for functional analysis, as long as the data acquisition window captures 18,257,[312][313][314][315][316] An assessment of MRI vs DSCT found that the function results were considered interchangeable. 210,317,318 When estimates of ventricular volumes and calculation of ejection fraction were compared to known volumes using a moving heat phantom and standard clinical imaging protocols, DSCT performed better than both MRI or 64 slice CT.…”
Section: Use Of Ct For Functional Imagingmentioning
confidence: 99%